DOI: 10.1007/978-3-540-75404-6_15
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 5 Degree-of-Freedom Towfish and Its Control Strategy

Abstract: Summary. This paper describes the development of a five degree of freedom towed underwater vehicle designed for condition monitoring of undersea pipelines. Its innovative design, with 6 fins actuated by 5 motors adding heave and sway capabilities to the yaw, roll and pitch movements possible in traditional designs, is explained. The parameters influencing the stability and the design in general are analyzed. A Control strategy for this design of highly coupled movements and control modes encompassing all the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Related studies on towed vehicles for various purposes can be found [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Research on improving the image of a sonar system mounted on a towfish [11][12][13] and obstacle avoidance for route tracking [14][15][16][17][18] were conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies on towed vehicles for various purposes can be found [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Research on improving the image of a sonar system mounted on a towfish [11][12][13] and obstacle avoidance for route tracking [14][15][16][17][18] were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, depth and attitude control using various controllers were studied [19][20][21][22][23][24][25][26]. Moreover, the vertical and horizontal shaking of a towed vehicle for monitoring submarine pipeline conditions [27] and turn maneuvering [28] are discussed. These studies are mainly focused aspects of the control method; however, the towfish is affected by various factors such as the towing point, position of the center of gravity, and towing speed.…”
Section: Introductionmentioning
confidence: 99%